Analysis of Evaluation System in different Departments at the College of Education: Addis Ababa University, Ethiopia - Assefa, Messeret (JOURNAL OF INDIAN EDUCATION, 2008)
Evaluation is the use of systematic gathering of information to learn about teaching and learning process. Addis Ababa University is moving from a summative to a continuous evaluation system. This study is an attempt to assess the extent to which the teachers adhere to continuous evaluation system in the University. The empirical basis of the study is a questionnaire-based investigation among the University teachers. The samples consist of forty teachers from different departments of College of Education, Addis Ababa University. The study also make an effort to compare the scores obtained by the students who were subjected to summative evaluation in 2005 and continuous evaluation during the first semester of 2006 which was completed in January 2006. The present paper elaborates about the background, objectives, methodology, sample and results of the study.